2018
DOI: 10.1002/anie.201808780
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of Methane and Carbon Dioxide Mediated by Diatomic Copper Boride Cations

Abstract: The use of CH and CO to produce value-added chemicals via direct C-C coupling is a challenging chemistry problem because of the inertness of these two molecules. Herein, mass spectrometric experiments and high-level quantum-chemical calculations have identified the first diatomic species (CuB ) that can couple CH with CO under thermal collision conditions to produce ketene (H C=C=O), an important intermediate in synthetic chemistry. The order to feed the reactants (CH and CO ) is important and CH should be fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 85 publications
0
24
0
Order By: Relevance
“…+ + CH4 and CuB + + CH4 is very instructive for the further study of the reactions between new transition-metal borides and methane. In both VB3 + and CuB + systems 42,43 , only the B atom is involved in the activation of the first C-H bond. For the VB + system, the H3C-H cleavage mainly takes place at the V-side through the synergistic insertion of V-B unit into the C-H bond.…”
Section: Fig 4 Dft Calculated Potential Energy Curves (Pecs) For Spimentioning
confidence: 99%
See 1 more Smart Citation
“…+ + CH4 and CuB + + CH4 is very instructive for the further study of the reactions between new transition-metal borides and methane. In both VB3 + and CuB + systems 42,43 , only the B atom is involved in the activation of the first C-H bond. For the VB + system, the H3C-H cleavage mainly takes place at the V-side through the synergistic insertion of V-B unit into the C-H bond.…”
Section: Fig 4 Dft Calculated Potential Energy Curves (Pecs) For Spimentioning
confidence: 99%
“…Recently, transition-metal boride cations have been discovered as a new category of active species for the thermal activation of methane 42,43 . Inspired by these findings, the diatomic vanadium boride cation (VB + ) has been studied to explore the feasibility of the early 3d transition-metal atom participating in the C-H bond activation of methane.…”
Section: Introductionmentioning
confidence: 99%
“…The nucleophilicity of gold is important in oxidative reactions, the Au − anion is more nucleophilic than Au(0), Au(I), and Au(III) species, and thus reactions of atomic Au − anions with hydrocarbons in the gas phase were studied [ 14 , 19 ]. The study of gas-phase ion-molecule reactions provides mechanistic insights into the bond-breaking and -making steps that are often obscured under condensed-phase environments, which are complicated by solvents, counterions, and ligands [ 14 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. Although gas-phase obtained information cannot replace that of the condensed phase, understanding the intrinsic unit makes it more feasible to improve chemical reactions or catalysts from a bottom-up approach [ 20 , 22 , 26 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al. demonstrated the use of a diatomic species (CuB + ) to mediate the direct C−C coupling reaction between CH 4 and CO 2 . Our recent work has shown that the radical anion of CO 2 (i.e., CO 2 .− ) can be inserted into the C−H bond of C 6 H 6 and eventually lead to the formation of benzoic acid .…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al demonstratedt he use of ad iatomic species (CuB + )t om ediate the directC ÀCc oupling reactionb etween CH 4 and CO 2 . [11] Our recentw ork has shown that the radical anion of CO 2 (i.e., CO 2 C À )c an be insertedi nto the CÀHb ond of C 6 H 6 and eventually lead to the formation of benzoic acid. [12] These findings suggest that ions, either cations or anions, in the gas phase may provide an alternative environment for CO 2 activation.A lthough af ree electron can easily activate CO 2 to form the radical anion CO 2 C À ,i ti sv ery difficult to manipulate CO 2 C À as ar eactanto ra ni nitiator of radical reactions due to its very short lifetime.…”
Section: Introductionmentioning
confidence: 99%